Digitalization of the Tourism Economy and Spatial Planning in the Environment oClimate Goals with the Approach of the Republic of Serbia, Montenegro and Croatia - Slobodan Nešković (International Scientific Journal "Monte")
This paper aims to explore the interaction between modern tourism, climate change, and spatial planning, with a particular focus on the application of digitalization and innovations in the tourism economy. The main goal is reviewing the key elements of the system of contemporary climate change and climate goals, politics and law in modern ambiences. The paper uses a methodological approach to consider digitalization phenomena in tourism and spatial planning in achieving existential climate goals. An overview is also given of the way of implementing global international obligations through the national regulations of Serbia, Montenegro and Croatia. The concepts of these countries are basically based on international regulation in this sphere with certain national specificities. We conclude that emphasizing the need for an integrated approach that combines digitalization, adaptation to climate change, and effective spatial planning to ensure the sustainable and prosperous development of modern tourism.